LEISURE, SAFETY, AND SUSTAINABILITY ON POST-PANDEMIC TOURISM: A SYSTEMATIC LITERATURE REVIEW - Ahmad Norma Permata; Sof Chal Jamiil; Atiyah Rauzanah Malik (Jurnal Sosiologi Reflektif, 2022)
Tourism is one of the most affected industries by the COVID-19 pandemic. Globally, in less than 6 months after the outbreak of the epidemic, this sector experienced a decline of up to 74%--as it set back to 1990s. However, many tourism-related studies include the keyword or even the title 'post-pandemic' which implies a nuance of optimism for the tourism sector. Using a systematic literature review (SLR), this article explores studies that include keywords and topics 'post-pandemic' in global and Indonesian contexts. Three main points were found: First, there is a global fact that local scale tourism is more sustainable than regional and international tourism. Second, behind the losses due to the decline in income during the pandemic, there is a hidden benefit in the form of restoring natural resources that have been damaged by tourism activities. Third, the emergence of a more systematic mapping of tourist preferences in determining tourist destinations and activities, which is more oriented towards safety, health, and strengthening social relationships with family and colleagues rather than excitement and offering lower cost discounts. The article also found that most post-pandemic tourism recommendations tend to be non-operational due to their failure to provide an operational definition of what the meaning of 'post-pandemic'.Pariwisata merupakan salah satu industri yang paling terdampak akibat pandemi Covid-19. Secara global, dalam waktu kurang dari 6 bulan setelah mewabahnya epidemi, sektor ini mengalami penurunan hingga 74%--kembali ke volume tahun 1990. Namun, banyak penelitian terkait pariwisata memasukkan kata kunci atau bahkan judul 'pasca pandemi' yang menyiratkan nuansa optimisme terhadap sektor ini untuk bangkit. Dengan menggunakan sistematika literature review (SLR), artikel ini mengeksplorasi kajian yang memasukkan kata kunci dan topik 'pasca-pandemi' dalam konteks global dan Indonesia. Tiga poin utama ditemukan: Pertama, adanya fakta global bahwa pariwisata skala lokal lebih berkelanjutan daripada pariwisata regional dan internasional. Kedua, di balik kerugian akibat penurunan pendapatan selama pandemi, terdapat keuntungan tersembunyi berupa pemulihan sumber daya alam yang telah rusak akibat kegiatan pariwisata. Ketiga, munculnya pemetaan preferensi wisatawan yang lebih sistematis dalam menentukan destinasi dan kegiatan wisata, yang lebih berorientasi pada keselamatan, kesehatan, dan penguatan hubungan sosial dengan keluarga dan rekan kerja daripada kegembiraan dan penawaran diskon biaya yang lebih rendah. Artikel tersebut juga menemukan bahwa sebagian besar rekomendasi pariwisata pasca-pandemi cenderung tidak operasional karena kegagalan mereka untuk memberikan definisi operasional tentang apa itu 'pasca-pandemi'.